(untitled) (Pakistan Journal of Science, 2022)
For the estimation of cycle time in WLANs different parameters were used to analyze the cyclic behavior like packet loss cycle, successful packet cycle and collision cycle. This paper proposes a model to control all the node activities, contention status, including collision probability, successful packet information, packet retransmission, packet loss information, cyclic behavior and throughput with comprehensive consideration of node heterogeneity. The simulation was performed for evaluation of proposed trace model and contention control scheme. The proposed model achieved significant results compared to existing schemes which did not systematically considered node heterogeneity. The results verified that the packet loss rate was 0%, collision probability was 7% and successful packet rate was 100%. The results varied due to the variance of successful sending of MAC Protocol Data Unit (MPDUs), total MPDU losses, total MPDU collision and the cyclic behavior.